Condition of surplus dairy calves during marketing: A cross-sectional study - H.L. Maggard; G.G. Habing; D.L. Renaud; K.L. Proudfoot; Z.A. England; T.-Y. Cheng; D.J. Wilson; M. Moran; J.A. Pempek (Journal of Dairy Science, 2024)
ABSTRACT: In North America, surplus dairy calves are sold soon after birth and often marketed through a third party (e.g., live auction, livestock dealer) before entering veal or dairy beef production. Previous work has demonstrated that a percentage of calves have failed transfer of passive immunity (FTPI) and clinical signs of disease on arrival at calf-raising facilities, but little is known regarding calf condition during marketing. The objectives of this cross-sectional study were to (1) estimate the prevalence of FTPI and poor health outcomes in surplus calves on arrival at livestock dealers, and (2) investigate the association between calf-level variables (body weight, sex, source) and health outcomes. Two livestock dealers in Ohio were visited 2 to 3 times per week, with approximately 28 calves enrolled in the study per visit for a total of 1,119 calves. One blood sample per calf was obtained to evaluate FTPI by measuring serum total protein concentrations (using a cutoff <5.1 g/dL). Calves were clinically evaluated for signs of arthritis, broken ribs or tail, dehydration, depression, diarrhea, fever, navel inflammation, and respiratory disease by 2 observers; health outcomes were dichotomized using clinically relevant cut points. Descriptive statistics were used to estimate the prevalence of calves with poor health outcomes. Multivariable logistic regression models were built to investigate the effect of body weight, sex, and source on health outcomes. Nineteen percent (206/1,091) of calves had FTPI.